An Investigation of the Relationship between Product Involvement and Consumer Decision-making Styles - ZHANG, YUE (2018)
The main purpose of this dissertation is to investigate the relationship between product involvement and consumer decision making styles. Sproles and Kendall (1986) propose the Consumer Styles Inventory (CSI) to measure the decision-making styles. But this overlooks product involvement. Based on the idea that consumers’ involvement in a specific product category moderates their decision-making style, this study explores Chinese consumers’ styles concerning yoghurt. It confirms a set of product-specific eight-factor decision-making styles and offers a new style of ‘Rational, seeking for value-for-money carefully’. The study illustrates that product involvement can moderate the consumer decision-making styles.